ANALISIS KOORDINASI STUDI KASUS: PT X - Victoria Sandroto, Indah
Abstract: Coordination plays an important role in combining many different divisions to achieve the common goal. In the context of today\'s organization management, company should keep surviving to face increasing competition, and highly environmental uncertainty. Unfortunately, coordination theory literature is still very few. The Organization Theory itself as the mother of the Coordination Theory is not believed yet to be claimed as a \"theory\". Therefore, the author conducts the case study research method. Case Study is aimed to make a deep exploration to certain company how coordination is done. A company has the goal, actors, dan activities. The author takes a case study at PT X PT X is a company in fashion business located in Jakarta. The research question which the author proposes are: (1) how the actors do the coordination of process ?, (2) how is the actor\'s mental model or cognition about the coordination of process ?, (3) why the company goal is not achieved ?, and (4) what recommendations or improvement needs to be implemented in order the parts of organization want to achieve the common goal ? The results of study showed that the company decomposes the goal that want to be achieved through activities and sub-activities. This decomposition is clear enough under the functional organization structure. Each division has its own task responsibility. To coordinate inter division, the company applies a coordination mechanism (the most important one): five coordination meetings per season. While performing operational activities, the company goal is not achieved because several conflicts: (1) conflict related to supplier relationship, (2) conflict due to coordination meeting mechanism, (3) conflict because of customer uncertainty. The author proposes recommendations so that PT X could improve internal coordination through considering: (1) focusing on Creative Division, or (2) applying situational coordination mechanism (flexible organization) related to the chosen strategy by PT X.